2011
DOI: 10.1159/000328426
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Autoimmune Hemolytic Anemia Associated with Multicentric Castleman Disease by Anti-Interleukin-6 Receptor Antibody (Tocilizumab) Therapy

Abstract: We describe herein the successful treatment of severe autoimmune hemolytic anemia (AIHA) in a patient with multicentric Castleman disease (MCD) by humanized anti-interleukin-6 (IL-6) receptor antibody (tocilizumab) therapy. Inflammatory anemia is commonly reported; however, AIHA is a very rare complication of MCD. In 1996, a 45-year-old Japanese woman was referred to our hospital because of generalized lymphadenopathy, anemia and skin eruptions. Lymph node biopsy demonstrated MCD. She was treated with predniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
(16 reference statements)
1
17
0
Order By: Relevance
“…These diseases include systemic autoimmune diseases such as systemic lupus erythematosus 74-76, systemic sclerosis 77, polymyositis 78, vasculitis syndrome including giant cell arteritis 79-84, Takayasu arteritis 79, 82, 85-87, cryoglobulinemia 88, myeloperoxidase-antineutrophil cytoplasmic antibody-associated crescentic glomerulonephritis 89 and rheumatoid vasculitis 90. The application of tocilizumab may also extend to organ-specific autoimmune diseases including Crohn's disease 91, relapsing polychondritis 92, 93, acquired hemophilia A 94, autoimmune hemolytic anemia 95, 96, as well as to chronic inflammatory diseases such as adult-onset Still's disease 97-113, amyloid A amyloidosis 114-120, polymyalgia rheumatica 79, 84, 121, remitting seronegative symmetrical synovitis with pitting edema 122, Behcet's disease 123, 124, uveitis 125, graft-versus-host diseases 126, 127, and tumor necrosis factor receptor-associated periodic syndrome 128 ( Table 1 ). Some studies have reported that tocilizumab is efficacious for spondyloarthritis 129-135, although others observed only minor effects 136-138.…”
Section: Targeting Il-6: All the Way To Treat Autoimmune And Inflammamentioning
confidence: 99%
“…These diseases include systemic autoimmune diseases such as systemic lupus erythematosus 74-76, systemic sclerosis 77, polymyositis 78, vasculitis syndrome including giant cell arteritis 79-84, Takayasu arteritis 79, 82, 85-87, cryoglobulinemia 88, myeloperoxidase-antineutrophil cytoplasmic antibody-associated crescentic glomerulonephritis 89 and rheumatoid vasculitis 90. The application of tocilizumab may also extend to organ-specific autoimmune diseases including Crohn's disease 91, relapsing polychondritis 92, 93, acquired hemophilia A 94, autoimmune hemolytic anemia 95, 96, as well as to chronic inflammatory diseases such as adult-onset Still's disease 97-113, amyloid A amyloidosis 114-120, polymyalgia rheumatica 79, 84, 121, remitting seronegative symmetrical synovitis with pitting edema 122, Behcet's disease 123, 124, uveitis 125, graft-versus-host diseases 126, 127, and tumor necrosis factor receptor-associated periodic syndrome 128 ( Table 1 ). Some studies have reported that tocilizumab is efficacious for spondyloarthritis 129-135, although others observed only minor effects 136-138.…”
Section: Targeting Il-6: All the Way To Treat Autoimmune And Inflammamentioning
confidence: 99%
“…Furthermore, excess production of interleukin-6 (IL-6) plays an important role in the pathogenesis of the CD (27). Giant lymph node hyperplasia is generally treated with surgery (28).…”
Section: Discussionmentioning
confidence: 99%
“…During the lytic phase, replication may be detected in the blood, and viral genes such as viral interleukin-6, are expressed. Most of the clinical effects of MCD are secondary to the presence of viral cytokines such as viral interleukin-6 [122][123][124] .…”
Section: Multicentric Castleman Diseasementioning
confidence: 99%